Thank you for the opportunity to help you with your question!
y = -1 and x = 1
wait i will send you the details
3x + y = 2
x - y = 2
x = 2 + y
we put x on the first equation :
3(2 +y) + y = 2
6 + 3y + y = 2
4y = -4
so : y = -1
we have to put y on one equation :
x - ( -1) = 2
x + 1 = 2
x = 1
if you don't understand just ask
i am glad to work with you just invite me each time
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?